Poultry feed metabolizable energy determination using total or partial excreta collection methods - LRB Dourado; JC Siqueira; NK Sakomura; SRF Pinheiro; SM Marcato; JBK Fernandes; JHV Silva (Brazilian Journal of Poultry Science, 2010)
The aim of this work was to compare the efficiency of total (TC) or partial (PC) collection excreta methods to determine metabolizable energy in poultry feeds. A number of 180 12- to 21-day-old broilers were distributed into two treatments of six replicates of 10 birds each. A reference-diet was formulated to supply broiler requirements, and the test-diets consisted of 60% of reference diets and 40% of corn or soybean meal. Celite was added at 1% to the diets as a marker. Excreta and diet samples were analyzed for dry matter, energy, nitrogen, and acid-insoluble ash (AIA). AME of corn determined by partial collection (PC) was higher (3544 kcal/kg) as compared to total collection (TC) (3133 kcal/kg). However, no difference were observed for soybean meal (1797 vs. 1821 kcal/kg) between both methods. Marker recovery rates in the excreta were 101, 111, and 96% for the basal-diet, and the test-diets with corn or soybean meal, respectively. This result indicates the importance of marker recovery rate in the excreta to evaluate feed AME and digestibility.